HOUSEHOLD DEMAND FOR ISLAMIC FINANCE IN SELECTED COUNTRIES - Sungur, Ozden (European Scientific Journal, ESJ, 2013)
The term Islamic Finance (IF) can generally be defined as the provision of financial services and products on the principles of Islamic shariah (law). Some basic principles of Islamic Finance are prohibition of riba (interest), gharar (uncertainty), and gambling. Another defining characteristic of Islamic Finance is that it is supposed to link financial transactions with activities in real economy and arrange for sharing of entrepreneurial risk. It is predicted by the International Organization of Securities Commission that by 2015, investments undertaken according to these principles will account for half of the savings of the world’s estimated 1.2-1.6 billion Muslims. Yet, we have very little insight into economic preferences of Muslim populations living in Western societies when it comes to shariah compliant investment opportunities. A 2010 report on Islamic Housing Finance in Canada commissioned by the Canada Mortgage and Housing Company notes that without such information it is impossible to understand how market demand would respond to an ever growing array of Islamic Finance products and services. This paper documents some stylzed facts about housing choices of immigrants in Italy as well as providing some comparison of the UK and the Canadian context. This is intended as a first step in uncovering household preferences for various investment alternatives among Muslim population in selected Western economies.